2022
DOI: 10.3390/su142113764
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Pools in a 77 Year-Old Oak Forest under Conversion from Coppice to High Forest

Abstract: Recent model projections and many research results across the world suggest that forests could be significant carbon sinks or sources in the future, contributing in a such a way to global warming mitigation. Conversion of coppice forest to high forest may play an important role towards this direction. This study deals with the estimation of biomass, carbon pool and accumulation rates in all IPCC biomass categories of a 77 year-old oak ecosystem, which has been subjected to conversion from coppice to high fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…More specifically, it was found to range from 5 cm to approximately 150 cm, which in turn resulted in great differences in stored carbon. However, the majority of carbon was found concentrated in the upper surface horizon up to the depth of ca 30 cm, as was reported in other studies (e.g., [22,34]. Recently, Balesdent et al [64] concluded through a meta-analysis that SOC dynamics and its responses to climatic changes or land use are strongly dependent on the soil depth.…”
Section: Soil Depthsupporting
confidence: 62%
See 1 more Smart Citation
“…More specifically, it was found to range from 5 cm to approximately 150 cm, which in turn resulted in great differences in stored carbon. However, the majority of carbon was found concentrated in the upper surface horizon up to the depth of ca 30 cm, as was reported in other studies (e.g., [22,34]. Recently, Balesdent et al [64] concluded through a meta-analysis that SOC dynamics and its responses to climatic changes or land use are strongly dependent on the soil depth.…”
Section: Soil Depthsupporting
confidence: 62%
“…In addition, there is no National Forest Soil Survey. In a recent study, Ganatsas et al [34] estimated an amount of ca 44 Mg C per hectare in a secondary degraded oak forest ecosystem under conversion, while Ganatsas and Papaioannou [35] reported much higher values for spruce and beech forest ecosystems in the Rhodope mountains, northern Greece. The present study aims to summarize the estimations of the total soil organic C accumulated in the whole soil depth, up to the stable bedrock, in a wide range of forest type ecosystems in Greece.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the natural forests are dominated by coppicing trees, which are short with small diameters, curved trunks, and low utilization. Ganatsas found that high forests exhibit significantly higher productivity and carbon storage capacity than coppice forests [5].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in forest carbon dynamics due to forest management practices have been often investigated and debated [10,[16][17][18]. Thus, prior studies on managed forests [19,20] showed that specific FMP can influence more or less the carbon balance along all pools (biomass, dead organic matter and soil) with potential implications on carbon mitigation [12,21]. Many studies have used different methodologies [22,23] and models [11,24,25] for the evaluation of carbon sequestration concerning various forest ecosystem properties and management practices [26][27][28].…”
Section: Introductionmentioning
confidence: 99%